Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus - Lima, Daniel Moura; Da Silva-Neto, Alberto Moreira; Aldrete, Alfonso N. García; Bravo, Freddy (Zootaxa, 2019)
A new Loneura species from the Brazilian state of Bahia (Loneura baiana n. sp.), is here described and illustrated. It is assignable to a species group of the genus but not to any of its subgroups. The previously unknown female of Loneura maracaensis Garcia Aldrete is described and illustrated, comments on variation in the fore- and hindwing venation of two male specimens of this species are included. Information on sexes known and distribution is included for all known species of Loneura.